Ductility reduction factor formulations for seismic design of RC wall and frame structures. (1st January 2019) - Zerbin, Matteo; Aprile, Alessandra; Beyer, Katrin; Spacone, Enrico
Highlights: Alternative formulation for computing force reduction factors for structures. Simple analytical models which only require available input data. Providing a variable force reduction factor not constant for a structural system. Obtaining a similar seismic performance for structures of different geometry. Providing a more accurate ductility reduction factor than current design approach. Abstract: Seismic design of standard structures is typically founded on a force-based design approach. Over the years this approach has proven robust and easily applicable by design engineers and – in combination with capacity design principles – it provides a good protection against premature structural failures. However, it is also known that the force-based design approach as it is implemented in the current generation of seismic design codes suffers from some shortcomings; among these is the fact that the base shear is computed using a pre-defined force reduction factor, which is constant for a given structural system. Thus, for the same design input, structures of an identical type but different geometry are subjected to varying ductility demands and may perform differently during an earthquake. The objective of this research is to present an alternative formulation for computing force reduction factors for RC wall and frame structures, using simple analytical models which only require input data already available at the beginning of the design process. Such analytical models allow to link global to local ductility demands and therefore to compute an estimate of the force ductility reduction factors that lead to equal local ductility demands and expected damage levels. A series of pushover and nonlinear time history analyses are run on simplified numerical models of a set of wall and frame structures. The results show that the proposed alternative formulation yields a more accurate ductility reduction factor than the current Eurocode 8 design approach.